2010
DOI: 10.1039/b915665h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tectonics: tubular crystals with controllable channel size and orientation

Abstract: The combination of flexible neutral organic tectons based on two pyridines interconnected by a thioether or thioester type spacer with an inorganic ZnSiF(6) pillar leads to the formation of 2-D coordination networks and the packing of the latter generates crystals offering controllable tubular channels with imposed orientation along the pillar axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…AA-α formed an AAAA layer arrangement similar to other sql topology HUMs (Figures 2, S5, and S6, some presented using simplified structures). 11,24,27,[41][42][43][44]51 S7). AB-α was found to exhibit ABAB stacking of layers, resulting in a pore structure distinct from that of AA-α and related materials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…AA-α formed an AAAA layer arrangement similar to other sql topology HUMs (Figures 2, S5, and S6, some presented using simplified structures). 11,24,27,[41][42][43][44]51 S7). AB-α was found to exhibit ABAB stacking of layers, resulting in a pore structure distinct from that of AA-α and related materials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Subsequently, some similar MOFs incorporating SiF 6 2− anions by using pyrazine or pyridine-based ligands to react with MSiF 6 (M = Co, Ni, Cu, Zn, Cd, et al) have also been reported one after another. [62][63][64][65][66][67][68] In these complexes, almost all the SiF 6 2− anions in these MOFs adopted the trans-coordination configuration to connect the M-ligand chains or grids into 2D networks or 3D frameworks with 1D square channels, and the structure assembled by the connection of SiF 6 2− with interpenetrated networks has never been reported. All these results clearly show that the coordination mode of SiF 6 2− anions with the metal cations has a great effect on the structure and porosity of MOFs, and the trans-coordination mode makes it more possible to generate porous polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Ligand B is inspired by chiral cyclohexyl based tectons 42 that have been used for the generation of chiral coordination networks in the crystalline phase. [43][44][45] Both ligands A and enantiomerically pure R,R-B (from now on just B) are obtained in a one-step reaction from commercially available reagents, following literature-reported procedures. [46][47][48][49] These simple building blocks are then combined with [Pd(MeCN) 4 ](BF 4 ) 2 in acetonitrile in a 1 : 1 : 1 ratio, yielding a rather structurally complex heteroleptic cage [Pd 2 A 2 B 2 ](BF 4 ) 4 (namely Pd 2 A 2 B 2 ; Scheme 1b).…”
mentioning
confidence: 99%